1109. Factors Impacting the Decision to Order Stool Diagnostic Testing in Patients With Acute Gastroenteritis Among Primary Care Providers. (26th November 2018) - O'Leary, Sean; Allison, Mandy; Cardemil, Cristina V; Hurley, Laura; Crane, Lori; Brtnikova, Michaela; Beaty, Brenda; Hall, Aron J; Pierre, Jeanette St; Ivey, Kathryn; Lindley, Megan C; Kempe, Allison
Abstract: Background: Diagnostic options for stool pathogens are evolving and expanding rapidly. The majority of acute gastroenteritis (AGE) patients seeking medical care are seen by primary care providers (PCPs), and stool testing may not be performed as AGE is generally self-limited. Little is known about how PCPs decide for which patients to order testing. Our objective was to describe among PCPs factors affecting the decision of whether to order stool diagnostic testing for pathogen detection in patients with AGE symptoms in the outpatient setting. Methods: A national survey was conducted from January to March 2018 among primary care pediatricians (Peds), family physicians (FP), and internists (GIM). Results: The response rate was 50% (689/1, 383; Peds 59% [275/466], FP 49% [226/461], GIM 41% [188/456]). Factors most often reported as greatly increasing the likelihood of testing that did not differ significantly between specialties included patient history of travel to a high-risk area (75% Peds, 71% FP, 72% GIM), immunocompromised patient (Peds 67%, FP 60%, GIM 69%), and clinical suspicion of a pathogen that can be treated with antibiotics or antiparasitics (Peds 63%, FP 56%, GIM 65%). Factors with significant differences between specialties that were most often reported as greatly increasing likelihood of testing included presence of blood in stool (Peds 76%, FP 58%, GIM 48%, P < 0.0001), history of recent antibiotic use (Peds 31%, FP 66%, GIM 72%, P < 0.0001), history of recent hospitalization (Peds 29%, FP 61%, GIM 64%, P < 0.0001), consideration of inpatient admission (Peds 36%, FP 57%, GIM 56%, P < 0.0001), and fever ≥38.5 C (Peds 13%, FP 27%, GIM 40%, P < 0.0001). Factors most often reported as greatly decreasing the likelihood of testing included presence of vomiting without diarrhea (Peds 49%, FP 43%, GIM 50%) and presence of vomiting and diarrhea together (Peds 12%, FP 7%, GIM 9%). Conclusion: Physicians rely on a variety of factors when considering diagnostic testing for stool pathogens in AGE, with recent travel, caring for an immunocompromised patient, and antibiotic/antiparasitic treatment decisions often reported as increasing the likelihood of testing. Consideration of the clinical presentation and most common AGE pathogens by age group may be driving some of the differences between specialties. Disclosures: All authors: No reported disclosures.